Talc based exopolysaccharides formulation enhancing growth and production of Hellianthus annuus under saline conditions - Tewari, S.; Arora, K. (Cellular and Molecular Biology, 2014)
Stress tolerating strain of Pseudomonas aeruginosa PF07 possessing plant growth promoting activity was screened for the production of exopolysaccharides (EPS). EPS production was monitored in the cell free culture supernatant (CFCS) and extracted EPS was further purified by thin layer chromatography. EPS producing cells were taken to design talc based formulation and its efficacy was checked on oilseed crop sunflower (Hellianthus annuus), under in vivo saline conditions (soil irrigated with 125 mM of saline water). Application of bioformulation significantly enhanced the yield and growth attributes of the plant in comparison to control (untreated seeds) under stress and non-stress conditions. Germination rate, plant length, dry weight and seed weight increased remarkably. The above findings suggest the application and benefits of utilizing EPS formulation in boosting early seedling emergence, enhancing plant growth parameters, increasing seed weight and mitigating stress in saline affected regions. Such bioformulation may enhance RAS/RT (Root Adhering Soil to Root Tissue ratio), texture of the soil, increase porosity, improve uptake of nutrients, and hence may be considered as commercially important formulation for renovation of stressed sites and enhancing plant growth.